Digital Literacy Analysis in Increasing Students’ Privacy Awareness as an Effort to Prevent Doxing Crimes in the Social Media Era - Bambang Mudjiyanto; Launa Launa; M. Daffa Shilbi; Afkar Khaibar Alfaruqi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to explore the significant role of digital literacy in enhancing students’ awareness of privacy as a preventive measure against doxing crimes, which remain a growing threat in the era of social media. Doxing, defined as the act of deliberately disclosing private information without consent, has increasingly targeted adolescent students who are active users of digital platforms. The research adopts a qualitative methodology with a descriptive-interpretive analysis and a phenomenological approach to deeply understand students’ experiences and perceptions. The findings illustrate that the level of students’ understanding regarding digital privacy, risky online behaviors, and preventive actions varies considerably. Digital education and literacy are shown to be effective in equipping students with the technical skills required to secure personal data and manage privacy settings on social media. In particular, students with higher exposure to digital literacy programs demonstrate better awareness of online threats and greater competence in identifying potential risks associated with doxing practices. Nevertheless, challenges persist. Peer pressure often influences adolescents to share excessive personal information online, undermining their privacy awareness. In addition, limitations in access to resources and the practical application of privacy-protection measures hinder students from fully implementing the knowledge they acquire. These barriers highlight the need for a more systematic and continuous approach to digital education. This study emphasizes that comprehensive digital literacy initiatives should not only focus on technical abilities but also foster a strong culture of privacy awareness. By doing so, students can be empowered to make responsible digital decisions, balance social interactions with personal security, and actively contribute to building a safer digital ecosystem. Overall, the research contributes to formulating strategies aimed at reducing the prevalence of doxing crimes by strengthening digital competencies and cultivating privacy-conscious behavior among adolescents.